Financial Behavior of Business on Sports Business Industry System: A Case Study of Liga One Football Club, PSSI - Uden Kusuma Wijaya; Muhammad Syahroni Rofii (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2022)
The purpose of this study is to discuss the financial practices and behavior of the sports business industry in Indonesia. The research location is the Liga One football club PSSI. What and how the financial and sustainability practices of football clubs in advancing the Indonesian sports business industry are studied by researchers. Are there interdisciplinary between these elements that form new needs and trends in the sports business? This study uses qualitative methods, including literature studies, interviews and limited discussions. The results show that the financial practice of football clubs focuses on the role of sponsors, media and football clubs. The behavior of sponsors and football club members is interconnected and plays a role in improving the financial side of the sports business in Indonesia